Coaching efficacy and coaching effectiveness in predicting athlete satisfaction: A self-other agreement framework - Chao, C.-H.; Kao, S.-F.; Tsai, C.-Y. (International Journal of Sports Science & Coaching, 2023)
The purpose of this study is to examine the relationships between coaching efficacy (i.e. coaches` efficacy beliefs) regarding their competence, coaching effectiveness (i.e. athlete's perception regarding their coaches` efficacy), and the athletes` level of satisfaction with their sport experience. As both coaches and athletes can have different evaluations of coaches` abilities, the different perspectives of coaches and athletes can reveal the dynamics within a coach-athlete dyad. We used 380 competitive college basketball coach-player dyads to determine the differences between coaching efficacy and coaching effectiveness. Drawing on the theoretical argument from the self-other agreement framework and self-enhancement bias, we hypothesize that coaching efficacy (i.e. measured from coaches) is higher than coaching effectiveness (i.e. measured from athletes) and that coaching effectiveness can better predict athlete satisfaction than coaching efficacy. We analyze our data using Welch t-test, random coefficient modeling, and polynomial regression with response surface methodology to test our hypotheses. Our results support our hypotheses such that coaching efficacy is significantly higher than coaching effectiveness and that other-ratings have a better predictive validity for athlete satisfaction, as self-ratings (coach's efficacy belief) could be inflated by self-enhancement. Our findings on athletes` perceptions highlight the importance of athlete-centric coaching mechanisms.